Management of urgent invasive procedures in patients treated with direct oral anticoagulants: An observational registry analysis. Issue 216 (August 2022) - Godon, Alexandre; Gabin, Manon; Levy, Jerrold H.; Huet, Olivier; Chapalain, Xavier; David, Jean-Stéphane; Tacquard, Charles; Sattler, Laurent; Minville, Vincent; Mémier, Vincent; Blanié, Antonia; Godet, Thomas; et al.
Abstract: Background: Patients treated with direct oral anticoagulants (DOACs) may require urgent procedures. Managing these patients is challenging due to different bleeding risks and may include laboratory testing, procedural delays, or haemostatic/reversal agent administration. Objective: We evaluated management strategies and outcomes of urgent, non-haemostatic invasive procedures in patients treated with DOACs. Methods and results: In a descriptive cohort study, we prospectively evaluated 478 patients in the GIHP-NACO registry, from June 2013 to November 2015. Hospitalised patients receiving dabigatran ( n  = 160), rivaroxaban ( n  = 274), or apixaban ( n  = 44) requiring urgent, procedural interventions were evaluated, of which 384/478 (80 %) were surgical procedures. Orthopaedic surgery included 216/384 patients (56 %), while gastrointestinal surgery included 75/384 (20 %) patients. On admission, the median age was 79 (70–85), and creatinine clearance was <60 mL·min −1 in 316/478 (66 %) patients. DOAC concentration was determined in 277 (58 %) patients and was 85 ng·mL −1 (median; range 0–764), 61 ng·mL −1 (3–541), and 81 ng·mL −1 (26–354) for dabigatran, rivaroxaban, and apixaban, respectively. Procedures were delayed in 194/455 (43 %) of the cases. Excessive bleeding was observed in 62/478 (13 %) procedures, and haemostatic agents were administered in 76/478 (16 %) procedures. By day 30, major cerebral and cardiovascular events were observed in 38/478 (7.9 %) patients, and mortality was 28/478 (5.9 %). Conclusions: In the GIHP-NACO registry, before specific antidotes were available, DOAC treated patients undergoing urgent invasive procedures were delayed in nearly half of the cases, and showed a low rate of excessive bleeding, suggesting that most urgent procedures can be performed safely without DOAC reversal. Clinical Trial Registration: www.ClinicalTrials.gov . Identifier: NCT02185027 Highlights: Management of direct oral anticoagulants is challenging in case of urgent invasive procedure. This study included 478 patients on DOAC requiring an urgent procedure, when specific antidotes were not available. Procedures were delayed in 42% of the cases, and excessive bleeding was observed in 13% of the cases. DOAC plasma concentrations were mainly low and were not associated with excessive bleeding.